Mechanical characterization of a 3D large strain zero Poisson’s ratio helical metamaterial - Cimolai, Guglielmo; Qin, Qing; Mageira, Pinelopi; Dayyani, Iman (Springer, 2025)
Mechanical metamaterials with zero Poisson’s ratio (ZPR) offer unique advantages in applications requiring dimensional stability under large deformations. Here we present a three-dimensional, large strain ZPR metamaterial composed of shape-optimized helical ligaments arranged in a hierarchical lattice. The design reduces stress concentrations at the joints and supports substantial elastic deformation in tension, compression and shear, while maintaining orthotropic, decoupled stress-strain behaviour. Finite element analyses assess homogenized properties, buckling behaviour, and vibrational modes through the analysis of the phononic band gaps, showing low normalized Young’s modulus and strain-invariant Poisson’s ratios. We further examine the influence of ligament cross-sectional diameter and the effect of different base materials on stiffness and strain range. Experimental tests on 3D-printed specimens confirm the predicted ZPR behavior and deformation capacity. The metamaterial’s elastic isotropy, fatigue resistance, and tailorable stiffness make it suitable for multifunctional applications including adaptive actuators, morphing structures, and energy-absorbing systems.
Supplementary information The online version contains supplementary material available at: https://doi.org/10.1038/s43246-025-00832-0.
Keywords: 40 Engineering; 4016 Materials Engineering; 3403 Macromolecular and materials chemistry